Revisiting the past to understand the present and future of soil health in Brazil - Silva, Antonio Marcos Miranda; Araújo, Victor Lucas Vieira Prudêncio de; Cardoso, Elke Jurandy Bran Nogueira (Frontiers in Soil Science, 2023)
As Soil Scientists, we are gathering important and valuable knowledge about the chemical, physical and biological processes in soil, and with the increasing effects of climate change, this knowledge may play a pivotal role in the future of our planet. However, we must revisit crucial points in our past to understand how humanity’s evolution has shaped the current state of soil health. Furthermore, we must also consider that we are funded and supported by the society in which we live, and therefore social and political factors will inevitably play a part in the future of soil health. In this review, we address important historical aspects of crop development and soil microbiome combined with the provision of key ecosystem services to ensure soil sustainability. In addition, we provide a brief overview of key concepts related to soil health, including the criteria of the selection of indicators for soil health assessment, whilst focusing on the role of soil biology. Moreover, we provide an overview of research conducted across diverse biomes in Brazil, highlighting approaches to assess soil health in both agroecosystems and natural ecosystems. We also emphasize the significance of harnessing beneficial plant-microorganism interactions as an ecologically sustainable strategy for enhancing soil health. Finally, we conclude the review by discussing potential advancements in soil health assessment in Brazil, and their potential application in broader agricultural and forestry contexts.